Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1149/1.1516413
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Control of Dy-Ni Alloy Films by Electrochemical Displantation

Abstract: The simultaneous control of morphology of Dy-Ni alloy was achieved by selective anodic dissolution of Dy in a molten LiCl-KCl-DyCl 3 ͑0.50 mol %͒ system at 700 K. The electrochemically formed DyNi 2 films, about 20 m thick, were transformed to porous Dy 2 Ni 7 , DyNi 5 , and Ni films, depending on the applied potential. Larger pores were formed when the applied potential was more positive. The rapidity and the pore-forming mechanism of the process are suggested to be closely related to the existence of the gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…The molten salt electrochemical process has been studied by Ito and co-workers including the present authors (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and many other researchers (13)(14)(15)(16). The present authors reported a unique phenomenon during the electrochemical formation of Dy-Ni alloys in molten LiCl-KCl-DyCl 3 : DyNi 2 film with thickness of 60 µm was formed in 2 h at 700 K (1).…”
Section: Introductionmentioning
confidence: 64%
“…The molten salt electrochemical process has been studied by Ito and co-workers including the present authors (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and many other researchers (13)(14)(15)(16). The present authors reported a unique phenomenon during the electrochemical formation of Dy-Ni alloys in molten LiCl-KCl-DyCl 3 : DyNi 2 film with thickness of 60 µm was formed in 2 h at 700 K (1).…”
Section: Introductionmentioning
confidence: 64%
“…Through electrochemical method in molten salts, Ln and their alloys can be prepared with high purity and more maneuverability [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] So far, various kinds of RE-TM alloys, where RE = Sc, Y, La, Ce, Pr, Nd, Gd, Tb, Dy, and Er, and TM = Fe, Co, Ni, and Pd, have been successfully obtained mainly from molten LiCl-KCl-RECl 3 systems at 723-773 K.…”
mentioning
confidence: 99%